(untitled) (Journal of Global Arts Studies, 2023)
Background: Currently the art of light and shadow is gradually being emphasized in creating immersive spatial experiences and has become an innovative trend in the field of modern spatial design. Objective: This paper aims to deeply analyze the role of light and shadow art in creating immersive experiences. Methods: By defining the concepts of light and shadow art and immersive experience, the study explores the key role of light and shadow art in the design of immersive experience and demonstrates its performance and advantages in practical application by analyzing a number of modern cases. Results: The study finds that light and shadow art can greatly enrich the audience’s experience by shaping the environmental atmosphere and enhancing sensory engagement. This art form not only provides visual aesthetics in immersive environments, but also combines functionality, awareness and interactivity. Conclusion: Light and shadow art plays an important role in the design of immersive experiences, and it shows significant potential and development trends in current and future spatial design, playing a key role in promoting innovation and uniqueness in modern spatial design.